Rehabilitation Service Needs and Preferences among Veterans with Tinnitus: A Qualitative Study - Clark, Khaya D.; Zaugg, Tara; DeFrancesco, Susan; Kaelin, Christine; Henry, James A.; Carlson, Kathleen F. (Seminars in Hearing, 2023)
Tinnitus is prevalent among military Veterans, yet there is a gap between the demand and the provision of services for tinnitus rehabilitation services within the Veterans Health Administration (VHA). We sought to understand tinnitus rehabilitation service needs and preferences among Veterans with bothersome tinnitus who use Veterans Affairs (VA) services. We conducted semistructured telephone interviews in 2019 with Veterans diagnosed with tinnitus, who reported it as bothersome. Veterans were purposively sampled to represent national VA users, with and without comorbid traumatic brain injury (TBI), and who were or were not interested in tinnitus rehabilitation services. Qualitative data were analyzed using a modified grounded theory approach. Among 40 Veterans interviewed (32 men, 8 women; 50% with TBI), 72.5% endorsed being somewhat/very likely to be interested in tinnitus rehabilitation services while 27.5% were very/somewhat unlikely. Themes related to Veterans' interest in tinnitus rehabilitation services included barriers and facilitators to participation and preferences for receiving tinnitus services (e.g., individual vs. group-based; in-person vs. remote access). Our findings highlight factors that influence Veterans' reported need and preferences for, and readiness to engage in, rehabilitation services for tinnitus. Personalized or otherwise adaptable approaches to program delivery may help ensure maximal uptake among Veterans.
Keywords: audiology; auditory rehabilitation; hearing healthcare; tinnitus; veterans